A life God rewards - Wilkinson, Bruce; Kopp, David, 1949- (Sisters, Or. : Multnomah, 2002)
Bruce Wilkinson shows you what Jesus said about God's plan to reward you in eternity for what you do for Him today. What you'll discover will unlock the power and potential of your life, starting now. And you'll begin to live with the unshakable certainty that what you do today matters...forever.
Keyhole to the Stars -- The Unbreakable Link -- What the Bible Says about Rewards -- That Day -- The Question of Your Life -- The God Who Gives Back -- The First Key -- Seeing through to Forever -- Christian Leaders on Eternal Rewards.
Includes bibliographical references (p. 124).
Keywords: Future life -- Christianity; Religion -- Christianity -- Christian Life